Foreign Aid, Donor Financing and Literacy Rate in Nigeria - Eze, A. E; Kalu, C.U; Okeyika, K.O; Mgbemena, O.O (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
While debates continues on the best way to deliver assistance, there is little doubt that Nigeria will continue to need significant aid to achieve development goals. Moreover, despite criticisms, aids has had many successes in Africa and Nigeria. This paper examined foreign aid, donor financing and literacy rate. This paper is anchored on the human capital theory and utilized the error correction model and the Granger causality approached over the period of 1985 to 2023. The variables of the paper are foreign aid, gross fixed capital formation, exchange rate, and inflation. The data for these variables were sourced from the Central Bank of Nigeria and National Bureau of Statistics (NBS). The result showed that foreign aid has a positive but insignificant impact on human capital development in Nigeria (P-values of t – statistics (0.058663) >Sig-value (0.005); trace statistic and the Max-eigenvalue statistic of Johansen co-integration test indicates 2 co-integrating equation(s) at the 5 percent level of significance indicating that there is a long-run relationship between foreign aid and literacy rate in Nigeria; also there is a uni-directional relationship between foreign aid and literacy rate. The paper recommended among others a policy framework that would guide against the country’s dependence on foreign aid beyond a point that may not be healthy for the economy.